Crohn's disease and its particularities: a literature review (Research, Society and Development, 2023)
Crohn's disease is an inflammatory disease of the gastrointestinal tract with a multifactorial etiology. Based on the severity of Crohn's Disease and the effect it causes on patients' quality of life, this paper aims to discuss its main clinical aspects, involving diagnosis and better professional management. A literature review was carried out with data collection through a bibliographic review for secondary surveys in the PUBMED, SCIELO and LILACS online databases. The incidence of Crohn's Disease (CD) between females and males is similar, ranging from 15 to 40 years old. It has the highest number of cases in Europe, North America and South America. There are several classifications for Crohn's Disease, and therefore it is the health professional's responsibility to know them, in order to know how to distinguish and carry out the correct drug prescription and treatment. Therefore, it is imperative that you are aware of the main characteristics, such as symptoms, etiology and preventive methods.